Squamous cell carcinoma of penis in patient with incipient neurosyphilis - D. V. Zaslavsky; Y. S. Egorova; I. N. Chuprov; A. B. Fedorchenko; G. L. Mareha; M. N. Fomenko; Y. Y. Gurkovskaya; S. I. Parxomenko; E. A. Timoshchuk; L. I. Kozlova; A. A. Sidikov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Squamous cell carcinoma of the skin (SSCC) is one of the most common malignant skin tumors. Syphilis is a sexually transmitted disease caused by Treponema pallidum, with human beings as the only host. The combination of syphilis and squamous cell carcinoma of the skin is not uncommon, particularly if the lesions are located on different parts of the body. However, simultaneous development of the chancre and squamous cell carcinoma of the glans penis seems exceptional. Considering rarity of the manifestation observed we feel the rare case of combined syphilis and squamous cell skin cancer is of interest.